Intronic variants in inborn errors of metabolism: Beyond the exome - Hertzog, Ashley; Selvanathan, Arthavan; Farnsworth, Elizabeth; Tchan, Michel; Adams, Louisa; Lewis, Katherine; Tolun, Adviye Ayper; Bennetts, Bruce; Ho, Gladys; Bhattacharya, Kaustuv (Frontiers in Genetics, 2022)
Non-coding regions are areas of the genome that do not directly encode protein and were initially thought to be of little biological relevance. However, subsequent identification of pathogenic variants in these regions indicates there are exceptions to this assertion. With the increasing availability of next generation sequencing, variants in non-coding regions are often considered when no causative exonic changes have been identified. There is still a lack of understanding of normal human variation in non-coding areas. As a result, potentially pathogenic non-coding variants are initially classified as variants of uncertain significance or are even overlooked during genomic analysis. In most cases where the phenotype is non-specific, clinical suspicion is not sufficient to warrant further exploration of these changes, partly due to the magnitude of non-coding variants identified. In contrast, inborn errors of metabolism (IEMs) are one group of genetic disorders where there is often high phenotypic specificity. The clinical and biochemical features seen often results in a narrow list of diagnostic possibilities. In this context, there have been numerous cases in which suspicion of a particular IEM led to the discovery of a variant in a non-coding region. We present four patients with IEMs where the molecular aetiology was identified within non-coding regions. Confirmation of the molecular diagnosis is often aided by the clinical and biochemical specificity associated with IEMs. Whilst the clinical severity associated with a non-coding variant can be difficult to predict, obtaining a molecular diagnosis is crucial as it ends diagnostic odysseys and assists in management.